Lamin A/C impairments cause mitochondrial dysfunction by attenuating PGC1α and the NAMPT-NAD+ pathway. Issue 17 (13th September 2022) - Maynard, Scott; Hall, Arnaldur; Galanos, Panagiotis; Rizza, Salvatore; Yamamoto, Tatsuro; Gram, Helena Hagner; Munk, Sebastian H N; Shoaib, Muhammad; Sørensen, Claus Storgaard; Bohr, Vilhelm A; Lerdrup, Mads; Maya-Mendoza, Apolinar; et al.
Abstract: Mutations in the lamin A/C gene ( LMNA ) cause laminopathies such as the premature aging Hutchinson Gilford progeria syndrome (HGPS) and altered lamin A/C levels are found in diverse malignancies. The underlying lamin-associated mechanisms remain poorly understood. Here we report that lamin A/C-null mouse embryo fibroblasts ( Lmna −/− MEFs) and human progerin-expressing HGPS fibroblasts both display reduced NAD + levels, unstable mitochondrial DNA and attenuated bioenergetics. This mitochondrial dysfunction is associated with reduced chromatin recruitment ( Lmna −/− MEFs) or low levels (HGPS) of PGC1α, the key transcription factor for mitochondrial homeostasis. Lmna −/− MEFs showed reduced expression of the NAD + -biosynthesis enzyme NAMPT and attenuated activity of the NAD + -dependent deacetylase SIRT1. We find high PARylation in lamin A/C-aberrant cells, further decreasing the NAD + pool and consistent with impaired DNA base excision repair in both cell models, a condition that fuels DNA damage-induced PARylation under oxidative stress. Further, ATAC-sequencing revealed a substantially altered chromatin landscape in Lmna −/− MEFs, including aberrantly reduced accessibility at the Nampt gene promoter. Thus, we identified a new role of lamin A/C as a key modulator of mitochondrial function through impairments of PGC1α and the NAMPT-NAD + pathway, with broader implications for the aging process.